Valuating frozen human embryo adoption from a moral philosophical point of view, lay ethics and two monotheist religions - Aznar, Justo; Martínez, Miriam; Navarro, Pedro (Acta Bioethica, 2016)
The search for IVF efficacy leads to a higher embryo production than it is necessary for implantation; this results in an excess of embryos which are kept frozen. This amount of frozen embryos inevitably increases. The donation/adoption are among the possible solutions for these frozen embryos. However, this practice has objective ethical problems. This article considers the ethical aspects of the donation/adoption of frozen human embryos from the point of view of moral philosophy, from what we could call "secular ethics" and from two monotheistic religions: Muslim and Jewish.